The winery: an exploration of the winery as catalyst for economic, social and tourism growth within the urban fabric - Goldring, Ryan (My University, 2011)
The theme of this thesis explores wineries and the unique quality that they possess of essentially being an industrial factory that has become a place of perceived romanticism, high class and sophistication. A curiosity of how a factory adopts such a prestigious and desired status is developed, and an exploration of whether the architecture of a winery has become such because of a collective romanticism and sophistication perceived by society and does architecture exaggerate this apparent imagery? Could a winery be understood on a multiple of levels and be able to trace an ‘architectural lineage’ to a typology that is already steeped in similar or perhaps seminary social readings? By using an understanding of ‘tourism theory’, an exploration of how the effect of tourism can infl uence the architecture of a winery and conversely how the winery, where void of the tourist, architecturally denounces the spatial glamour generally presented to the tourist and returns to being a factory. By utilising this new understanding of a winery, the question is asked of whether a winery can serve a larger collective of society and not an exclusive few. By doing so, the winery could be re-scripted and be transformed from a factory space to space of sophistication to ultimately a space of social contribution